The exegetical encounter between Jews and Christians in late antiquity - Grypeou, Emmanouela; Spurling, Helen (Jewish and Christian perspectives series ;, 2009)
This collection of essays examines exegetical encounters between Christians and Jews on the book of Genesis. Eminent scholars present outstanding studies on the subject of a ~Exegetical Encountera (TM) to illuminate the history of relations between Jews and Christians in Late Antiquity.